The Relationship Between Knowledge, Attitude and Perception With Behavior In Consuming Herbal Medicine in Singaraja City - Ariantini, Nyoman Sri; Solehah, Eka Lutfiatus (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: The emergence of various diseases such as the COVID-19 pandemic is now causing the public to seek various treatments and to strengthen the body's immune system. The transmission of the virus through local transmission causes the number of COVID-19 cases to continue to grow. Therefore, prevention efforts must be made, namely the breaking of the chain of transmission with self-isolation, early detection, and basic protection. The basic excretion referred to by other children washing hands regularly with soap or using hand sanitaizer, maintaining distance, and consuming healthy foods to improve the immune system.Purpose: This study aimed to find out the relationship between knowledge, attitude and perception with behavior in consuming herbal medicine.Methods: The design of this study is observationally descriptive with a crossectional approach. Singaraja city has an area of 27.98 km2, and its population of 80,500 people is used the type of probability sampling technique simple random sampling. The sample is calculated by the formula obtained as many as 100 respondents. The data was collected with questionnaire instruments and analyzed with chis square tests.Results: The results showed a value of ? for knowledge, attitude and perception < ? then this shows a relationship between knowledge, attitude and perception with behavior in consuming herbal medicine.Conclusion: The community still gives a positive response to traditional medicine through herbal medicine. This happens because the public already knows enough about the benefits of consuming herbal medicine that can maintain and increase immunity especially in the pandemic period this is needed.